KEMAMPUAN SARI BUAH NANAS MUDA DALAM PENGGUMPALAN PROTEIN SUSU SAPI TERHADAP KARAKTERISTIK KIMIA TAHU SUSU - S., OLIVIA; S. A., LINDAWATI; DEWANTARI, M. (Fakultas Peternakan Universitas Udayana, 2023)
The purpose of this study was to determine the ability of young pineapple juice to coagulate cow’s milk protein on the chemical characteristics of milk tofu. The design used was a completely randomized design (CRD) with four treatments and four replications, each replication using 1000 ml of cow’s milk. The four treatments were: the ad- dition of 30 cc of young pineapple juice (P1), the addition of 40 cc of young pineapple juice (P2), the addition of 50 cc of young pineapple juice (P3), and the addition of 60 cc of young pineapple juice (P4). The observed variables were chemical characteristics which included protein content, fat content, water content, and pH value. Research data were analyzed using variance, if the effect of treatment was significantly different (P <0.05), then continued with Duncan’s multiple distance test. The results showed that the protein content of milk tofu in treatment P4, P3, and P2 was not significantly different (P>0.05) compared to treatment P1, but in treatment P4 was significantly (P<0.05) 18.58% higher. and 13.82% compared to treatments P3 and P2. Fat content, water content, and pH values in all treatments (P4, P3, P2, and P1) showed no significant difference (P> 0.05). The conclusion of this study was the ability of young pineapple juice to coagulate cow’s milk protein on the chemical characteristics of milk tofu and its effect on protein content, but had no effect on fat content, water content, and pH value. The concentration of 30 cc of young pineapple juice has good chemical characteristics with protein content of 26.84%, fat content of 50.01%, water content of 64.14% and pH value of 6.31.